EVALUASI PAMERAN BUKU TAHUN 2017 SAMPAI DENGAN 2019 DISELENGGARAKAN OLEH PERPUSTAKAAN FAKULTAS EKONOMI UNIVERSITAS ISLAM INDONESIA - Suwardi, Suwardi FBE UII (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2021)
The book exhibition organized by the Fakultas Ekonomi Universitas Islam Indonesia Library Division is a form of community service especially for the FE UII academic community. This event is regularly held once a year and is part of a series of UII anniversary events. To improve the quality of implementation, evaluation is necessary, according to Bertrand the appropriate model is an assessment model for the media. The evaluation method used is descriptive qualitative. Primary data were obtained through interviews and observations, and secondary data were obtained from literature studies in accordance with the intended topic. The assessment of the exhibition by participants and visitors follows an assessment model of the media which consists of five components, namely attraction, acceptability, comprehension, self involvement and persuation. The collected data about the exhibitions were confirmed by the theory referred to, and also confirmed with the opinions of visitors and exhibitors through direct interviews. The results of the evaluation show that the components of attraction, acceptability, self involvement and persuation are in accordance with expectations, while the components of comprehension are not yet optimal.